Peran Kompetensi Pegawai dan Komitmen Organisasi dalam Memediasi Manajemen Sumber Daya Manusia pada Kinerja Organisasi - Sofiyanto, Azhar; Rachmansyah, Yanuar; Sutanto, Himawan Arif (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2023)
Good organizational performance not only helps organizations achieve competitive advantage but also creates a healthy, innovative and growth-oriented environment. The aims of this study were: (1) to analyze the influence of human resources management on organizational performance, employee competency and organizational commitment; (2) analyzing the effect of employee competence and organizational commitment on organizational performance; (3) analyzing the role of mediating organizational competence and commitment to the relationship between human resources management and organizational performance. The object of this research is the Staffing and Human Resources Development Agency of Tegal Regency. Sampling is done by census or saturated sample of 50 employees. Structural Equation Modeling – Partial Least Square (SEM-PLS) analysis was used to analyze data using SmartPLS 4. The results showed that HR management had a positive and significant effect on organizational performance, employee competency, and organizational commitment. Employee competence and organizational commitment have a positive and significant effect on organizational performance. Employee competency and organizational commitment are able to mediate the relationship between Human Resources Management and Organizational Performance